Visual perception skills: a comparison between patients with Noonan syndrome and 22q11.2 deletion syndrome. (23rd May 2017) - Piccini, G.; Menghini, D.; D'Andrea, A.; Caciolo, C.; Pontillo, M.; Armando, M.; Perrino, F.; Mandolesi, L.; Salerni, A.; Buzzonetti, L.; Digilio, M. C.; Zampino, G.; et al.
Abstract : Ventral and dorsal streams are visual pathways deputed to transmit information from the photoreceptors of the retina to the lateral geniculate nucleus and then to the primary visual cortex (V1). Several studies investigated whether one pathway is more vulnerable than the other during development, and whether these streams develop at different rates. The results are still discordant. The aim of the present study was to understand the functionality of the dorsal and the ventral streams in two populations affected by different genetic disorders, Noonan syndrome (NS) and 22q11.2 deletion syndrome (22q11.2DS), and explore the possible genotype–phenotype relationships. 'Form coherence' abilities for the ventral stream and 'motion coherence' abilities for the dorsal stream were evaluated in 19 participants with NS and 20 participants with 22q11.2DS. Collected data were compared with 55 age‐matched controls. Participants with NS and 22q11.2DS did not differ in the form coherence task, and their performance was significantly lower than that of controls. However, in the motion coherence task, the group with NS and controls did not differ, and both obtained significantly higher scores than the group with 22q11.2DS. Our findings indicate that deficits in the dorsal stream are related to the specific genotype, and that in our syndromic groups the ventral stream is more vulnerable than the dorsal stream. Abstract : Our results indicated that there is a specific relationship between differential genotype and phenotype. In detail, in the motion coherence task, the performance achieved by the group of children with Noonan syndrome (NS) and the controls was significantly better than the performance achieved by children with 22q11.2 deletion syndrome. However, the performance of groups of children with genetic syndromes was equivalent for the form coherence task and significantly lower than the performance of the control group. This dissociation in the syndromic groups seems therefore indicative of a better information processing ascribed to the dorsal occipital‐parietal stream in children with NS and suggests that the ventral stream is more vulnerable than the dorsal stream in our syndromic groups.